A CASE FOR BUILDING EMPLOYEE KNOWLEDGE-BASED COMPETITIVENESS AND POSITIVE ROLES FOR ESTABLISHING LEGACY IN AN EDUTECH COMPANY - Siti Yasmina Zubaedah; Sophia Reni Susilo; Livia Evangelina Florencia (LPPM Universitas Abdurrab, 2025)
Qualified human resources can develop the necessary knowledge and skills, thereby enhancing a company's competitive position in the industry. With a total of 35 participants, comprising Accelist employees at various levels within the organization, ranging from staff to managerial levels, the community service was organized as an online seminar format. The seminar commenced with presentations of academic material by Management faculty members. For quantitative measures, the community service concluded with a feedback survey to gather participants’ perceptions on the effectiveness of the activity. The individual lecturer’s average score of over three, based on a scale of 1 – 4, reflected participants’ positive perceptions and indicated an overall effectiveness of the community service in meeting their requirements. In addition to providing a complete documentation of the community service, this article was intended to inspire and provide guidance for industry workers to develop valuable legacy and apply working with impact. The community services presented illustrate the value of university-industry collaborations, particularly in the field of human resource development.